Understanding microwave pyrolysis of biomass materials - Adam, Mohamed A.B. (2017)
Global challenges related to energy security, resource sustainability and the environmental impacts of burning fossil fuels have led to an increasing need for switching to the use of clean and sustainable resources. Bio-oil produced through pyrolysis has been suggested as one of the sustainable alternatives to fossil resources for power generation as well as chemicals and biofuels production. Pyrolysis is a thermochemical process during which the biomass feedstock is heated in an inert atmosphere to produce gas, liquid (bio-oil) and solid (char) products. Microwave heating has been considered a promising technique for providing the energy required for biomass pyrolysis due to its volumetric and selective heating nature which allows for rapid heating in a cold environment. This helps to preserve the product quality by limiting secondary reactions. The aim of this research was to study the interactions between biomass materials and microwave energy during pyrolysis, and to develop a reliable and scalable microwave pyrolysis process. The dielectric properties of selected biomass materials were studied and found to vary significantly with temperature due to the physical and structural changes happening during pyrolysis. The loss factor of the biomass materials was found to reach a minimum value in the range between 300 oC and 400 oC followed by a sharp increase caused by the char formation. A microwave fluidised bed process was introduced as an attempt to overcome the challenges facing the scaling-up of microwave pyrolysis. The concept of microwave pyrolysis in a fluidised bed process was examined for the first time in this thesis. A systematic approach was followed for the process design taking into account the pyrolysis reaction requirements, the microwave-material interactions and the fluidisation behaviour of the biomass particles. The steps of the process design involved studying the fluidisation behaviour of selected biomass materials, theoretical analysis of the heat transfer in the fluidised bed, and electromagnetic simulations to support the cavity design. The developed process was built, and batch pyrolysis experiments were carried out to assess the yield and quality of the product as well as the energy requirement. Around 60 % to 70 % solid pyrolysed was achieved with 3.5 kJ·g-1 to 4.2 kJ·g-1 energy input. The developed microwave fluidised bed process has shown an ability to overcome many of the challenges associated with microwave pyrolysis of biomass including improvement in heating uniformity and ability to control the solid deposition in the process, placing it as a viable candidate for scaling-up. However, it was found to have some weaknesses including its limitations with regards to the size and shape of the biomass feed. Microwave pyrolysis of biomass submerged in a hydrocarbon liquid was introduced for the first time in this thesis as a potential alternative to overcome some of the limitations of the gas-based fluidised bed process. Batch pyrolysis experiments of wood blocks submerged in different hydrocarbon liquids showed that up 50 % solid pyrolysis could be achieved with only 1.9 kJ·g-1 energy input. It was found that the overall degree of pyrolysis obtained in the liquid system is lower than that obtained from the fluidised bed system. This was attributed to the large temperature gradient between the centre of the biomass particle/block and its surface in the liquid system leaving a considerable fraction of the outer layer of the block unpyrolysed. It was shown that the proposed liquid system was able to overcome many of the limitations of the gas-based systems.